Genetic variation for grain phytate and molecular characterization of low phytic acid‐2 (lpa2) gene‐based maize (Zea mays) inbreds. (13th February 2022) - Ragi, Shridhar; Muthusamy, Vignesh; Zunjare, Rajkumar U.; Bhatt, Vinay; Katral, Ashvinkumar; Abhijith, Krishnan P.; Chand, Gulab; Mishra, Subhra J.; Sekhar, Javaji C.; Yadava, Devendra K.; Hossain, Firoz
Abstract: Maize possesses higher concentration of phytic acid (PA) compared with other cereals, reducing bioavailability of iron and zinc. Reduction of PA in maize grains thus assumes significance to alleviate micronutrient malnutrition. Here, a set of 24 inbreds possessing mutant lpa2‐1 gene and seven inbreds with wild‐type LPA2 gene was field evaluated at Delhi and Hyderabad. The performance of lpa2‐1 ‐based inbreds was at par with wild‐type inbreds for grain yield ( P = .09645) and key agronomic traits ( P > .54100). Mutant inbreds possessed significantly low mean PA (1.90 mg/g) over wild‐type inbreds (2.56 mg/g) ( P < .00001), with average reduction of 26% PA among lpa2‐1 mutants. Mean inorganic phosphorous (iP) was 0.81 mg/g in lpa2‐1 mutants and 0.27 mg/g in wild types, revealing significantly ( P < .00001) higher increment (three‐fold) of iP in mutants compared with wild‐type inbreds. Characterization using 61 simple sequence repeats (SSRs) generated 181 alleles with mean polymorphism information content of 0.40 and mean gene diversity of 0.46. Cluster analyses grouped lpa2‐1 inbreds into three‐major clusters. The study identified potential cross combinations for development of low phytate maize with higher bioavailability of iron and zinc.